Prediction of locally advanced bladder tumor using preoperative clinical parameters - Syah Mirsya Warli; Fauriski Febrian Prapiska; Dewi Indah Sari Siregar; William Saputra Wijaya (Urology Annals, 2023)
Background: Staging of bladder cancer (BC) still remains a challenge. In conjunction with imaging, there is a critical need for accessible and cost-effective predictors to evaluate the existence of locally advanced disease. Objective: Our aim was to determine the role of preoperative clinical parameters in predicting locally advanced cT3/4 and/or cN+ in BC. Materials and Methods: Single-center data consisting of 32 patients were collected prospectively and eligible for the final analysis. The demographics data, presence of hydronephrosis, and results of renal function test (blood urea nitrogen [BUN] and serum creatinine [SCr]) were analyzed between the groups. Analysis of the receiver-operating characteristics curve was performed to determine the optimal cutoff value, sensitivity, and specificity of the preoperative clinical parameters, whereas multivariate logistic regression was used to assess the predictive analysis. Results: According to preoperative computed tomography imaging, 17 (53.1%) out of 32 patients with BC had locally advanced disease. Preoperative hydronephrosis and renal insufficiency as indicated by BUN and SCr levels were independently associated with the presence of locally advanced disease (P < 0.05). Multivariate analysis confirmed that the presence of preoperative hydronephrosis and higher level of BUN and SCr were the independent predictors of locally advanced BC (Odds ratio [OR] =6.6; 95% confidence interval [CI]: 1.40–31.05; P = 0.017; OR = 6.6; 95% CI: 1.40–31.05; P = 0.017; OR = 18.67; 95% CI: 3.16–110.29; P = 0.001, respectively). No further variables were statistically significant. Conclusion: Preoperative assessment of hydronephrosis and renal insufficiency was able to predict locally advanced stage risk of BC cT3/4 and/or cN+; thus, preoperative staging might be improved. However, further studies are required to corroborate these findings.